Student Management at Saint Aloysius School Dormitory - Antsa Rinaldi Rafaliarisoa; Cepi Safrudin Abdul Jabar (Universitas Negeri Yogyakarta, 2020)
This study aims to obtain an understanding of the student management at the Saint Aloysius school dormitory in the Special Region of Yogyakarta, Indonesia. The research applied a case study research method. It mainly involves the participation of four caretaker team members and ten students. The obtained data were collected through techniques, such as interviews, observations and document analysis. The research study involves the application of three concurrent data analysis techniques. The research led to the knowledge and the understanding that despite the dormitory’s geographical location and its small size, the caretakers at the involved school dormitory make an effort to provide most of the services and tasks required for an effective student management.Generally, the student management implemented at this specific school dormitory involves the establishment of different tasks and services. Important factors, including staff supervision and training, the establishment of the formal program, also need to be considered by the caretakers. Caretakers still need to make some effort to improve management services.